Monitoring arthritis with flex sensor - Ng, Yuan Lin (Nanyang Technological University, 2021)
This final report documents the process of building a monitoring system for arthritis patients. The aim of this project is to monitor the condition of an arthritis patient with the use of flex sensors. This monitoring system will analyze data with the use of previous current and previous data. The patients will also be informed of the results. Furthermore, the results can also be retrieved at any point both locally and remotely by any medical personnel or the patient.